A comparative study of cognitive impairment in sporadic and familial cases of multiple sclerosis - Vida Niakosari; Ali Namjoo-Moghadam; Ahmad Ali Abin; Maryam Poursadeghfard; Sana Hashemi (Scientific Reports)
Abstract Genetics plays a significant role in Multiple Sclerosis (MS), with approximately 12.6% of cases occurring in familial form. While previous studies have demonstrated differences in disease progression and MRI findings between familial and sporadic MS, there has been no comparison of cognitive impairment between them. In this study, we evaluated cognitive performance among patients with sporadic and familial MS, along with a healthy control group. A total of 130 individuals, matched for age, sex, and education, were recruited for each group. The mean age of participants was 37.8 ± 9.8 years, and 77.6% of them were female. Cognitive performance was assessed using the Brief International Cognitive Assessment for MS (BICAMS) across the three groups. Both familial and sporadic MS patients showed poorer cognitive performance in the Symbol Digit Modalities Test (SDMT) (Familial: 46.96 ± 12.59, Sporadic: 45.88 ± 14.13, Normal: 56.48 ± 11.89), California Verbal Learning Test (CVLT) (Familial: 66.90 ± 14.01, Sporadic: 68.19 ± 16.49, Normal: 75.18 ± 13.02), and the Brief Visuospatial Memory Test-Revised (BVMT-R) (Familial: 24 (12), Sporadic: 24 (12), Normal: 35 (4)) compared to healthy controls. Meanwhile, no significant differences in cognitive impairment were observed between the familial and sporadic MS groups in the SDMT (p = 1.000), CVLT (p = 0.775), and BVMT-R (p = 0.733). Furthermore, this study found significant relationships between education, depression, age, and sex with different aspects of cognitive performance in MS. Overall, both familial and sporadic MS patients demonstrated similar levels of cognitive impairment.